Application of SVD Method Using Magnetic Data to Identify Subsurface Structures at the Geothermal Area of Sonai Village and its Surroundings, Puriala, Konawe - La Ode Andimbara; Wa Ode Salmatia; Abdul Manan; Bahdad; Rani Chahyani (Jurnal Ekologi, Masyarakat dan Sains, 2025)
This research was conducted with the aim of identiying the subsurface structures of the geothermal area of ??Sonai Village and its surroundings, Puriala, Konawe using the Second Vertical Derivative (SVD) method. The magnetic data used were obtained through measurements at 126 points. The total magnetic anomaly value obtained after Diurnal and IGRF corrections was -171.17 to 82.47 nT. After carrying out Upward Continuation and further processing, a residual magnetic field anomaly value of around -150 to 90 nT was obtained. Then the SVD method is applied to residual anomalous data that has been reduced to the Pole. Based on the SVD results and 2D modeling, several types of fault structures were found in the research area, consisting of 2 upward faults and 4 normal faults. The closest minor fault to the manifestation is at coordinates 4°1'16.41"S and 122°7'23.23"E which is ±16 meters from the manifestation. These minor faults are thought to be the geothermal pathways, causing the water to become hot in the manifestation area. In addition, it was also found that the subsurface layers of the Sonai area and its surroundings are composed of 3 formations, namely Alluvium Deposits, Alangga Formation and Ultramafic Complex.